(untitled) (Sustainability in Debate, 2025)
The impact of mining on residential rents is a significant concern in mining regions. This study examined the impact of negative externalities from mining companies Vale and Samarco on rental prices in Ouro Preto, Minas Gerais, in 2023. To achieve the proposed objective, a hedonic pricing model was estimated. The results showed that the closer a property is to mining activities, the lower its rental value, indicating a depreciation of real estate values. The conclusions suggest that mining externalities affect the local real estate market, which is relevant for the creation of public policies that balance economic development and the mitigation of the negative impacts of mining.